From Face-To-Face to the Online Space: The Continued Relevance of Connecting Students With Each Other and Their Learning Post COVID-19 - Garrad, Traci-Ann; Page, Angela (Frontiers in Education, 2022)
At the time of writing, the largest state in Australia is once more in complete lockdown because of surging cases from the new variant strain of COVID-19. During the last lockdown in early 2020, we conducted a study analysing the efficacy of mapping best-practice face-to-face university teaching into the online space. This article reports on the results of a survey from the perspective of student belonging. Isolation was the most prevalent theme recorded by students despite not being one of the research questions asked. The importance of adopting the model in online university courses in the current/post-COVID-19 world is presented.